TEPX as a high-precision luminosity detector for CMS at the HL-LHC. (1st March 2022) - Haranko, M.; Auzinger, G.; ,
Abstract: The CMS BRIL project upgrades its instrumentation for the Phase-2 detector to provide high-precision luminosity and beam-induced background measurements. A part of the CMS Inner Tracker — the Tracker Endcap Pixel Detector (TEPX) — will allocate a fraction of the read-out bandwidth for luminometry. The implications of the proposed approach are highlighted. A dedicated luminosity trigger and clock distribution system is introduced and a test implementation on a demonstrator system is described. A demonstrator of the real-time on-FPGA pixel cluster counting algorithm is also described.